Optical Forces: From Fundamental to Biological Applications. Issue 37 (26th July 2020) - Xin, Hongbao; Li, Yuchao; Liu, Yong‐Chun; Zhang, Yao; Xiao, Yun‐Feng; Li, Baojun
Abstract: Optical forces, generally arising from changes of field gradients or linear momentum carried by photons, form the basis for optical trapping and manipulation. Advances in optical forces help to reveal the nature of light–matter interactions, giving answers to a wide range of questions and solving problems across various disciplines, and are still yielding new insights in many exciting sciences, particularly in the fields of biological technology, material applications, and quantum sciences. This review focuses on recent advances in optical forces, ranging from fundamentals to applications for biological exploration. First, the basics of different types of optical forces with new light–matter interaction mechanisms and near‐field techniques for optical force generation beyond the diffraction limit with nanometer accuracy are described. Optical forces for biological applications from in vitro to in vivo are then reviewed. Applications from individual manipulation to multiple assembly into functional biophotonic probes and soft‐matter superstructures are discussed. At the end future directions for application of optical forces for biological exploration are provided. Abstract : Optical forces form the basis for optical trapping and manipulation, and are of critical importance in various disciplines from fundamental research to practical applications. Advances in optical forces have made significant impact for biological exploration both in vitro and in vivo, with applications from individual manipulation and analysis to multiple assembly and detection.